(3GdCHcGQ GdMSGf aj PcQ ehGgH GdQMefs - (3GHcQ Hf Ydj eUdMs
(3ChdgG (B:s
(3CeG HYO , aEfg deG cGf jhe GdCQHYGA YGe NeS hSHYjf heGFJjf HYO GdCda fhjJ Cf CLeY HYV cdGe dHYV aUMGA CHfGA GdYUQ GdMGFRjf bUH GdSHb hGdMcGjGJ eY GdHTGQGJ s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg ai MQa GdjGA bhdg (B: (3hCeG ai gPg GdCYhGe GdbQjHI abhehf GdSfjf hcPG GdeDQNhf hGdeHTQhf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs